Assessing the effects of a DPP IV inhibitor and risperidone on behavioural interactions and lipid peroxidation in a mouse model of induced autism - Sudan, Ahmed; Ali, Yousef; Jihad, Safa; Howaidy, Sabreen (Pharmakeftiki, 2025)
The autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by early-onset deficits in communication and social interaction. This study investigated the effects of a dipeptidyl peptidase-4 (DPP IV) inhibitor, sitagliptin, in a murine model of ASD induced by prenatal exposure to sodium valproate (VPA). In order to evaluate ASD-like behaviours, an open field test (OFT) was conducted so as to assess locomotor activity and anxiety-related responses. The antioxidant and anti-inflammatory properties of sitagliptin were examined by quantifying levels of reduced glutathione, malondialdehyde (MDA), and interleukin-6. VPA-exposed mice were allocated into four experimental groups: (i) saline control, (ii) VPA + sitagliptin (DPP IV inhibitor), (iii) VPA + risperidone, and (iv) VPA-only. Behavioural assessments via OFT were performed on postnatal day 65, followed by biochemical analyses of oxidative stress and inflammatory markers on postnatal day 66. Sitagliptin treatment significantly attenuated oxidative stress and neuroinflammation, leading to marked improvements in aberrant behavioural phenotypes. It exhibited pronounced anxiolytic effects, ameliorating ASD-associated symptoms such as anxiety, hyperactivity, and fearfulness in the OFT. Furthermore, sitagliptin demonstrated superior antioxidant efficacy compared to risperidone, notably in reducing lipid peroxidation. A dose of 10 mg/kg of sitagliptin yielded significant reductions in MDA levels, underscoring its free radical scavenging potential. These findings suggest that sitagliptin may offer a promising therapeutic strategy for mitigating core and associated symptoms of ASD.